STUDI ETNOBOTANI TUMBUHAN YANG DIMANFAATKAN DI DESA PESAGUAN KANAN KECAMATAN MATAN HILIR SELATAN KABUPATEN KETAPANG - Liyanti, Puspita Resi; Budhi, Setia; Yusro, Fathul (Universitas Tanjungpura, 2015)
The utilization of plants as a source of life that is done in order to fulfill the daily needs with the ability to adapt, will try to satisfy their needs according to availability around them. The ethnobotany of traditional use of plants by the community is essential to keep the knowledge of their wisdom in the use of plants. This study aims to determine the types and parts of plants used by rural communities Pesaguan Kanan. The benefits of the research are expected to maintain the existing knowledge in the community to develop forest resources. This research is using snowball sampling method tointerview by the number of respondents as many as 60 people. Data from interviews conducted directly are analyzed in order to obtain results in the form of a systematic and accurate description. From the results of research there are 200 species of plants which are grouped into 76 families consisting of food plants 91 species, medicinal plants 73 species, coloring material plants 7 species, plant pesticide plant 3 species, ornamental plants 56 species, fodder plants 9 species, wood-producing plants 10 species, plant materials 12 species, plant producing rope, webbing and crafts 14 species. Based on the results, it turned out that one kind of plant has more than one benefit. Advice given is that there is a need for the availability of useful plants in the forest and around the community.Keywords: Ethnobotany, Plant used, Pesaguan village, Identification